2017
DOI: 10.1242/dev.152033
|View full text |Cite
|
Sign up to set email alerts
|

Dmrt1 induces the male pathway in a turtle with temperature-dependent sex determination

Abstract: The molecular mechanism underlying temperature-dependent sex determination (TSD) has been a long-standing mystery; in particular, the thermosensitive genetic triggers for gonadal sex differentiation are largely unknown. Here, we have characterized a conserved DM domain gene, Dmrt1, in the red-eared slider turtle Trachemys scripta (T. scripta), which exhibits TSD. We found that Dmrt1 has a temperature-dependent, sexually dimorphic expression pattern, preceding gonadal sex differentiation, and is capable of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 60 publications
3
91
1
Order By: Relevance
“…In non-mammalian vertebrates, estrogen and its synthetase aromatase play an important regulatory role in early gonadal sex differentiation. Exogenous estrogen and aromatase inhibitor (AI) can override the effects of primary sex-determination signals, including genetic and environmental factors, if applied during critical developmental periods (Crews 1994a; Crews 1994b; Smith et al 2003; Schulz et al 2007; Kobayashi et al 2008; Ge et al 2017;). Treatment of AI onto chicken ZW eggs was able to induce upregulation of Dmrt1 , a Z chromosome-linked master sex-determining gene, ultimately resulting in female-to-male sex reversal (Smith et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-mammalian vertebrates, estrogen and its synthetase aromatase play an important regulatory role in early gonadal sex differentiation. Exogenous estrogen and aromatase inhibitor (AI) can override the effects of primary sex-determination signals, including genetic and environmental factors, if applied during critical developmental periods (Crews 1994a; Crews 1994b; Smith et al 2003; Schulz et al 2007; Kobayashi et al 2008; Ge et al 2017;). Treatment of AI onto chicken ZW eggs was able to induce upregulation of Dmrt1 , a Z chromosome-linked master sex-determining gene, ultimately resulting in female-to-male sex reversal (Smith et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese soft-shelled turtle Pelodiscus sinensis (P. sinensis) exhibiting ZZ/ZW genetic sex-determining system has been recently emerged as an ideal turtle model for investigating reptilian sex determination and differentiation, due to the well-established genetic modulation technique (Sun et al 2017; Ge et al 2017) and available genome resource (Wang et al 2013). In this study, we found that knockdown of Mis by RNA interference resulted in male-to-female sex reversal in P. sinense .…”
Section: Introductionmentioning
confidence: 99%
“…A key and evolutionarily conserved regulator of male specific gene expression and antagonist of female fates that is necessary for male-specific development is the Double sex and Mab3 related transcription factor, Dmrt1 [11,[43][44][45][46][47][48][49][50]. Mutants lacking dmrt1 develop mostly as fertile females -the opposite phenotype of rbpms2DMs [11].…”
Section: Epistasis Analysis Between the Female Factor Rbpms2 And Malementioning
confidence: 99%
“…Ge et al. () recently used lentiviral vectors to manipulate Dmrt1 expression in red‐eared slider turtles. Knockdown Dmrt1 at a male‐producing temperature increased aromatase expression, while overexpression of Dmrt1 at a female‐producing temperature reduced aromatase expression.…”
Section: Critical Evaluation Of the Literaturementioning
confidence: 99%
“…Indeed, temperature effects on Cirbp and Dmrt1 expression occur before changes in aromatase expression in snapping turtles (Rhen et al, 2007;Schroeder et al, 2016). Ge et al (2017) Knockdown of Sox9 mRNA and protein expression at a male-producing temperature reduced Amh expression, showing that Sox9 directly or indirectly regulates Amh. However, Sox9 knockdown did not increase aromatase expression.…”
Section: Yolk Steroids At Ovipositionmentioning
confidence: 99%